Warthin tumour: a case report and approach in primary care - Radin Abdul Halim, Radin Siti Hajar; Md Aris, Mohd Aznan; Abd Fuaat, Azliana (UniKL Royal College of Medicine Perak (UniKL RCMP), 2024)
Warthin tumour (WT) is an infrequent benign salivary gland neoplasm, that primarily occur in the parotid gland, the largest of the salivary glands. Comprising roughly 15% of all salivary gland tumours, these lesions are the second most prevalent type of salivary gland neoplasm after pleomorphic adenoma encountered in clinical practice. Here, we report a case of Warthin tumour of six years’ duration in a 46-year-old male patient in the left parotid gland and will discuss the diagnostic process, differential diagnoses, and management of a suspected WT in a primary care setting. While Warthin tumours are generally considered to be non-malignant, they can mimic carcinomas in terms of their glandular size and appearance. As such, it is crucial for primary care providers to be able to recognize and appropriately manage these lesions.